1‐Ethynyl Ethers as Efficient Thermal Crosslinking System for Hole Transport Materials in OLEDs. (26th October 2016) - Limberg, Felix R. P.; Schneider, Tanja; Höfle, Stefan; Reisbeck, Felix; Janietz, Silvia; Colsmann, Alexander; Krüger, Hartmut
Abstract : A new crosslinking concept based on a thermally activated one‐component building block with thermally initiated crosslinkable ynol ether is introduced. For polystyrene matrices with glass transition temperatures below the reaction temperature, full conversion is reached within 30 min at 160 °C without employing any catalysts or co‐reactants. The ynol ethers are chemically inert toward a variety of reaction conditions (e.g., radicals and strong bases) and consequently applicable to a wide range of materials for organic electronics. The crosslinkable solid compounds are bench‐stable over more than a year. The broad applicability is demonstrated with a liquid model compound and a specifically designed crosslinking monomer introduced successfully as building block into polystyrenes with pending hole transporting groups. A detailed study of crosslinking kinetics by infrared measurements as well as an alternative method of crosslinker content determination utilizing differential scanning calorimetry is presented. The crosslinkable polymer and the corresponding noncrosslinkable molecule tris(4‐(3, 6‐dibutoxy‐ 9H ‐carbazol‐9‐yl)phenyl)amine (BuO6 TCTA) are synthesized and investigated as hole transport layers (HTLs) in phosphorescent organic light emitting diodes (OLEDs). OLEDs with crosslinked and noncrosslinked HTLs show efficiencies around 80 cd A −1, indicating negligible influence of the crosslinking process on the device performance while yielding better HTL durability against solvent rinsing. Abstract : 1‐Ethynyl ethers are introduced as crosslinkers for solution processable hole transport materials in organic light emitting diode (OLED) applications. Thermally initiated crosslinking proceeds at 160 °C within 30 min quantitatively. 1‐Ethynyl ethers are introduced as polymerizable styrene monomers and co‐polymerized with styrene functionalized hole transport groups (m‐BuO4 TCTA). The co‐polymers are fully bench‐stable and the corresponding OLEDs yield high efficiencies.